Two new species of Dilobopterus Signoret, 1850 and the male of D. segmentalis (Signoret, 1853) from Southeastern Brazil, with taxonomic notes on the genus (Hemiptera: Cicadellidae: Cicadellini) - Quintas, Victor; Felix, Márcio; Lima, Douglas Felipe Dos Santos; Mejdalani, Gabriel (Zootaxa, 2017)
Two new species of Dilobopterus Signoret, 1850 are described from the Atlantic Rainforest of Rio de Janeiro State, Southeastern Brazil, based on specimens collected in Angra dos Reis (D. nelsoni sp. nov.) and Itatiaia (D. sakakibara sp. nov.). Holotypes are deposited in Museu Nacional, Universidade Federal do Rio de Janeiro. These are the first species of the genus described after the publication in 1977 of the last comprehensive monograph on the New World Cicadellini. We also describe the previously unknown male of D. segmentalis (Signoret, 1853) based on specimens from the Atlantic Rainforest of Espírito Santo State, Southeastern Brazil (municipality of Santa Teresa). We propose a group of species within Dilobopterus (trinotatus group) based on features of the paraphyses of D. trinotatus (Signoret, 1853), D. segmentalis, and D. sakakibara sp. nov..